Stories of Change and Innovation in the Volta Basin Development Challenge Program - Greenough, Karen Marie (CGIAR Challenge Program on Water and Food, 2014)
Innovation seems to be the lead buzz-word of the 2010 decade, a must for funding proposals. In this report, to go beyond buzz words and dictionary definitions, I try to tell stories of change and innovation within the Volta Basin Development Challenge, or CPWF-Volta, of CGIAR’s Challenge Program for Water and Food. The stories about change and innovation told in this report come from the people involved in the VBDC: the project team members and project participants. Has the VBDC produced innovations? The answer to that question would seem to depend on how one defines and perceives the changes in knowledge, practices and relationships of VBDC stakeholders. These definitions and perceptions depend on context and point of view. We found that different people, of different statuses, see innovation in different lights, but also that the VBDC projects have produced many changes. It is too early to say whether they will persist as innovations in the eyes of outside evaluators, but many in- country researchers and facilitators have seen and experienced what they call innovations in their partnerships with VBDC.